Analyzing the Impact of Eco-Innovation on Carbon Emissions Abatement: Evidence from OECD Countries - Chen, Yinfei; Mkumbo, Rebeca Nasolwa (International Journal of Sustainable Development & World Policy, 2020)
This present study aimed to assess the impact of eco-innovation on carbon emission abatement in OECD countries. However, 34 OECD countries were sampled in a panel to carefully understand the phenomenon. The data for the study were sourced from OECD database and World Bank’s World Development Indicators from 2005 to 2018. Numerous econometric approaches were followed to arrive the conclusion of this study. Econometric approaches such as unit root rests, correlation matrix, cointegration test, Granger causality test, ordinary least square regression method, and fully modified ordinary least square regression method. The findings of the study suggest that eco-innovation could positively and negatively impact carbon emission abatement regarding the kind of proxy used. From the findings, it was realised that energy intensity, and patents positively impact carbon emission abatement, hence a percentage point increase in energy intensity could lead to an increase in carbon emission by 0.677% and 0.705% while a percentage increase in patent could also lead to 0.073% and 0.087% of carbon emission, respectively. On the other hand, research and development expenditure seemingly contribute to carbon emission abatement, where a percentage point increase in research and development expenditure could lead to 0.032% carbon emission abatement. This implies that increase in real income could encourage research and development and reduce energy intensity. Moreover, to ensure low carbon economy, conservation policies that support reduction in energy intensity, strengthening of environmental regulations, and improving research and development should be encouraged.